1983
DOI: 10.2134/jeq1983.00472425001200040002x
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Precipitation Effects on Crops: A Review and Analysis of Research

Abstract: For more than a century it has been known that vegetative growth is affected by the products of fossil fuel combustion. Recently, the acidic deposition phenomenon has gained increasing attention, especially when implicated as a factor responsible for economic loss. Research has been directed toward quantification of effects; however, limitations in the design of many crop studies restricts the usefulness and applicability of the results. Acidic deposition varies in a number of ways that may affect crop yield (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…The reason for this is unclear and has been reported by other reseachers. 12 Evans and coworkers 13 reported that even the method by which rain is applied can affect the growth response. The proposed mechanisms by which acid rain may affect growth are reviewed by McLaughlin 14 and Morrison.…”
Section: Growth Responsementioning
confidence: 99%
“…The reason for this is unclear and has been reported by other reseachers. 12 Evans and coworkers 13 reported that even the method by which rain is applied can affect the growth response. The proposed mechanisms by which acid rain may affect growth are reviewed by McLaughlin 14 and Morrison.…”
Section: Growth Responsementioning
confidence: 99%
“…The Mitscherlich model was explored as an alternative to functions which have been used to model plant response to ozone 8 because the Mitscherlich has natural biological interpretations for its parameters and it has been applied previously to model plant growth response to the supply of nutrients. The Mitscherlich function is intuitively more satisfactory than a plateau-linear model 2 because it does not assume the existence of a sharp break in response. Although the Mitscherlich function is a generalized model that fits many types of data, it would not be appropriate for data that demonstrates a stimulatory effect at low concentrations (quadratic relationship).…”
Section: Methodsmentioning
confidence: 99%
“…3 ' 4 Nor have the effects of growth conditions on exposureresponse functions been evaluated even though there is reason to believe that environmental conditions change plant response to acidic rain. 6 Disagreement in results between laboratories performing research on acidic rain may be due to many factors 2 and the contribution of different treatment and growing conditions to the divergency of results is not known.…”
mentioning
confidence: 99%
“…The negatively charged nitrate and sulphate ions in acid rain may act as "counter-ions," which allow cations such as potassium (K + ), sodium (Na + ), calcium (Ca 2+ ) and magnesium (Mg 2+ ) to be leached from the soil and become unavailable to plants (Ivring, 1983). This will probably lead to nutrient deficiency.…”
Section: Introductionmentioning
confidence: 99%